Effects of Androgen Deprivation Therapy on COVID-19 in Patients with Prostate Cancer: A Systematic Review and Meta-Analysis - Karimi, Amirali; Nowroozi, Ali; Alilou, Sanam; Amini, Erfan (Urology Journal, 2021)
Purpose: Transmembrane serine protease 2 (TMPRSS2) facilitates SARS-CoV-2 cellular entry. Androgens regulate this protein and may increase the risk of COVID-19. Therefore, androgen deprivation therapy (ADT) may protect patients with prostate cancer from SARS-CoV-2 infection or decrease the severity of the disease. Therefore, we conducted a meta-analysis to study the effect of androgen deprivation therapy (ADT) on COVID-19 in patients with prostate cancer. Methods: We systematically searched PubMed, Embase, Scopus, and Cochrane databases. All records underwent a two-step screening process to identify the eligible studies. The registered PROSPERO number of this study was CRD42021228398. We evaluated the effect of ADT on the risk of infection, hospitalization, ICU admission, and mortality. Results: Six studies met inclusion criteria and were evaluated in this study. We performed meta-analysis on four eligible studies. The overall incidence of COVID-19 was 2.65% among patients with prostate cancer receiving ADT. COVID-19 mortality rate was about 22.7% in ADT (+) patients. ADT did not decrease the risk of any of the major outcomes; infection risk (OR= 0.63, 95% CI= 0.27- 1.48, P = 0.29), hospitalization rate (OR= 0.51, 95% CI= 0.10- 2.53, P = 0.41), ICU admission (OR= 1.11, 95% CI= 0.43- 2.90, P = 0.82), and mortality risk (OR= 1.21, 95% CI= 0.34- 4.32, P = 0.77). Conclusion: We did not observe a protective effect on the risk of infection, hospitalization, ICU admission, and mortality in patients receiving ADT; therefore, it should not be considered as a prophylactic or treatment for COVID-19. On the other hand, ADT did not increase the mortality and morbidity of COVID-19 and should be considered a safe treatment for patients with prostate cancer during the pandemic. Further studies are necessary to confirm our findings.